2010
DOI: 10.1017/s1041610210000827
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases in peripheral blood and cerebrospinal fluid in patients with Alzheimer's disease

Abstract: These findings constitute further evidence for the important role of MMPs in the pathogenesis of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 29 publications
3
61
1
2
Order By: Relevance
“…Understanding how MMPs are regulated developmentally during the period of neuronal death may lead to new strategies for preventing neurodegenerative diseases. Genes for MMPs are associated with neurodegenerative diseases (36), and up-regulation of MMPs is reported in patients with Alzheimer disease (37,38) and in animal models of Parkinson disease (39,40). The experimental system we have developed may provide a model to define the molecular mechanism linking ECM signals to survival of neurons in disease.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding how MMPs are regulated developmentally during the period of neuronal death may lead to new strategies for preventing neurodegenerative diseases. Genes for MMPs are associated with neurodegenerative diseases (36), and up-regulation of MMPs is reported in patients with Alzheimer disease (37,38) and in animal models of Parkinson disease (39,40). The experimental system we have developed may provide a model to define the molecular mechanism linking ECM signals to survival of neurons in disease.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-3, for example, has been detected around senile plaques, in the grey matter and in the interstitium between myelinated axons and astrocytes in the white matter of AD patients [387]. MMP-3 is also significantly elevated in the plasma and CSF of AD patients [388]. More recently, the CSF of cognitively-healthy individuals with risk markers for future AD has been found to have higher MMP-3 levels and a higher MMP-3/TIMP-1 ratio than healthy individuals without risk markers [389].…”
Section: C) Alzheimer's Diseasementioning
confidence: 99%
“…Consistent with these findings, several groups found overexpression of MMP-2, -3, and -9 mRNA and protein in postmortem brains from AD patients. [221][222][223][224] Horstmann et al 225 used zymography and detected MMP-2, -3, -9, and -10 activity levels in serum and CSF from AD patients and compared them to gender-and age-matched healthy control individuals. The authors found that MMP-3 activity was elevated by 40% in plasma and 60% in CSF from AD patients compared to control individuals.…”
Section: Alzheimer's Diseasementioning
confidence: 99%